Analysis Of Door Placement At Business Area In Semarang Chinatown - Soteria Adia Mahanaim; Bayu Widiantoro (TUTURRUPA, 2020)
A design speaks not just through visuals, but instead, a design speaks through anything around us. One of the things that had existed since a long time ago is culture. Culture plays a significant role where it is unique on its own place giving impact to the environment. In this case Semarang Chinatown is a place where the Chinese Culture shows genuinely. It is intriguing that door placement of business building have a same placement in Semarang Chinatown. This research is a qualitative study obtained from related data from direct observations and literature. The data obtained will be used to prove what kind of Chinese Culture that influences door placement of business building in Semarang Chinatown.Keywords: culture, door placem